Research on transaction privacy protection solutions for cross‐border commerce - Ma, JinCheng; Li, Fei (IET blockchain, 2024)
In response to the dual privacy protection challenges concerning the confidentiality of transaction amounts and identities in cross‐border trade, a transaction scheme that combines +HomEIG Zero Knowledge Proof (+HomEIG‐ZKProof) and the national encryption algorithm SM2 is proposed. While ensuring transaction traceability and verifiability, this scheme achieves privacy protection for both payers’ and recipients’ identities, specifically tailored for cross‐border trade scenarios. Additionally, customs authorities play the role of supervisory nodes to verify the identities of transaction parties and the zero‐knowledge proofs for transaction information. The RAFT consensus algorithm is employed to construct a secure authentication application, demonstrating how zero‐knowledge proofs, combined with homomorphic encryption, can be verified through a consensus process. In this scenario, the legitimacy of transaction amounts is subject to zero‐knowledge verification during consensus interactions. Merchant identity verification is accomplished using SM2 ring signatures. The analysis indicates that this scheme offers strong security features such as resistance to tampering attacks, public key replacement attacks, impersonation attacks, and anonymity. Testing results demonstrate that this scheme can effectively provide dual privacy protection for transaction amounts and identities in cross‐border trade, meeting the practical requirements of privacy protection in cross‐border trade transactions. This article explores the application of a Consortium Blockchain in cross‐border commercial trade transactions, emphasizing privacy protection. It introduces an innovative approach that combines the +HomEIG Zero‐Knowledge Proof with the SM2 algorithm to enhance transaction security and privacy. This method addresses the challenges of maintaining confidentiality and integrity in cross‐border trade, making it a significant contribution to the field of blockchain‐based trade solutions.